Implementasi Energi Terbarukan pada Sistem Kelistrikan Kapal Nelayan - Edy Prasetyo Hidayat; Imam Sutrisno; Ari Wibawa Budi Santosa; Fahmi Umasangadji; Ardiansyah; Fais Hamzah; Nafi Almuzani; Urip Mudjiono (CV. Creative Tugu Pena, 2025)
This study investigates the application of renewable energy—specifically solar panels and wind turbines—in the electrical systems of fishing vessels. The research methodology includes literature review, power demand analysis, simulations, and experimental trials on a prototype fishing vessel. The findings demonstrate that integrating renewable energy systems can reduce fuel consumption by up to 30% and significantly improve operational efficiency. The adoption of a hybrid solar and wind energy system enables fishing vessels to remain at sea longer without complete reliance on fossil fuels. This study makes a notable contribution to the field of marine electrical systems and renewable energy by developing and validating a sustainable, energy-efficient onboard power system through a comprehensive empirical approach—ranging from technical design and simulation to field implementation. Key outcomes include a 30% reduction in fuel use and an increase in system efficiency to 85%, offering a practical solution for lowering operational costs among small-scale fishermen. The research also advances theoretical understanding of renewable energy integration in the maritime sector, which has predominantly focused on large commercial vessels. The incorporation of lithium-ion–based energy storage systems in small Indonesian fishing vessels presents a novel approach with significant development potential, particularly in addressing geographic and energy access challenges in remote coastal communities. These results provide a foundation for formulating government policies on subsidies and incentives to support the transition to green energy in the national fisheries sector.